Representasi Pejabat Pemerintah terhadap Kebijakan Lockdown Pada Tayangan ILC TV One - Yustitiayu Novelly; Siska Andes Madya; Ngusman Abdul Manaf (Ranah: Jurnal Kajian Bahasa, 2021)
The purpose of this study is to see how the representation of government officials about the pros and cons of lockdown by those who are pro with the policy of government officials; and how the representation of government officials about the lockdown counter by those who are counter to the policy of government officials in conveying their ideology in a speech on the ILC TV ONE talk show with the theme Corona: Pro and Counter Lockdown. This type of research is qualitative research with descriptive methods. The data in this study were in the form of speeches from each of the speakers, namely government officials and experts. The subjects in this study were government officials and experts who were the speakers at the ILC TV ONE program. The approach of this research is AWK Norman Fairclough's qualitative approach. The results of this study indicate that, that there is no one vote whether the pros or cons lockdown. Because there are a lot of considerations and shadows if the lockdown is done what the impact is and if nothing is done. There are 3 findings of representation from government officials' statements on the lockdown policy, namely (1) Government officials in their speeches do not have strong control to make decisions, local government officials still play it safe and maintain respect for the government above it. (2) Central government officials, which are represented by the President's spokesman, can only provide an educational explanation on what is social distancing and what is lockdown and the policies that are carried out; and (3) Representative government officials and experts criticizing the policies taken by the government have not been maximized and are not firm. AbstrakTujuan penelitian ini adalah untuk mengungkapkan bagaimana representasi pejabat pemerintah  tentang pro dan kontra lockdown oleh pihak yang pro dengan kebijakan pejabat pemerintah; dan bagaimana representasi pejabat pemerintah tentang prokontra lockdown oleh pihak yang kontra dengan kebijakan pejabat pemerintah dalam menyampaikan ideologinya dalam tuturan di talk show ILC TV ONE dengan tema Corona: Pro dan Kontra Lockdown. Jenis penelitian ini adalah penelitian kualitatif dengan metode deskriptif. Teknik analisis data yang digunakan dalam penelitian ini adalah analisis wacana kritis model Norman Fairclough yang meliputi teks, discourse practice, dan sociocultural practice. Pendekatan penelitian ini berupa pendekatan kualitatif prespektif AWK Norman Fairclough. Hasil penelitian ini menunjukkan bahwa, bahwa tidak satu suara apakah pro atau kontra lockdown. Karena banyak pertimbangan dan bayangan-bayangan jika lockdown dilakukan apa dampaknya dan jika tidak dilakukan apapula dampaknya. Ada 3 temuan representasi dari tuturan pejabat pemerintah atas kebijakan lockdown, yaitu (1) Pejabat pemerintah dalam tuturannya tidak mempunyai kendali yang kuat untuk membuat keputusan, pejabat pemerintah daerah masih bermain aman dan menjaga kehormatan kepada pemerintah diatasnya. (2) Pejabat pemerintah pusat yaitu diwakili oleh jubir Presiden hanya bisa memberikan penjelasan pendidikan mengenai apa itu sosial distancing dan apa itu lockdown serta kebijakan yang dilakukan; dan (3) Pejabat pemerintah wakil rakyat dan pakar mengkritisi kebijakan yang diambil pemerintah belum maksimal dan tidak tegas.